Exploring the English Language Skills Needed at Engineering Companies - Aswirawan, Maria Yosefina Meinadia Sekar Kinanti; Lawi, Ansarullah (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
This paper reports the results of an English language needs analysis carried out at different multinational engineering companies in Batam, Indonesia. Through the implementation of needs analysis questionnaire to 50 engineers from various engineering companies, the perceived importance and frequency of linguistic needs of learners in terms of skills and sub-skills are specified. The results show that most engineers perceived reading as the most important skill, followed by listening, writing, and speaking; whereas, in terms of frequency, reading has also been perceived as the most frequent skill, followed by listening, writing and speaking. Emphasis should be put on receptive skills (a total mean score of 16.048) rather than productive skills (a total mean score of 15.423). However, findings also depict those engineers considered some of the oral communicative event(s) such as reporting work to superiors to be very frequent at work. The implications of the findings indicate that materials design and development should consider the incorporation of workplace scenarios as the basis for activities.